Restoring Halite Fluid Inclusions as an Accurate Palaeothermometer: Brillouin Thermometry Versus Microthermometry - Guillerm, Emmanuel; Gardien, Véronique; Ariztegui, Daniel; Caupin, Frédéric (Geostandards and geoanalytical research, 2020)
Halite traps inclusions of the mother fluid when precipitating. When unchanged, the density of these fluid inclusions (FIs) records the water temperature Tf at the time of crystal formation. As halite is ubiquitous on Earth and geological time, its FIs possess a high potential as temperature archives. However, the use of FIs in halite as an accurate palaeothermometer has been hampered due to limitations of microthermometry, the most commonly used analytical method. Here, we show how Brillouin spectroscopy in halite FIs bypasses these limitations and allows recovering Tf to within 1 °C or less. To demonstrate this, we measured samples synthesised at 24.6 ± 0.5 °C and 33 ± 1 °C, and obtained 24.8 ± 0.4 °C and 31.9 ± 0.4 °C, respectively. This novel approach thus provides an accurate palaeothermometer for lacustrine and marine environments. Moreover, Brillouin spectroscopy solves the long‐standing debate on damage of halite fluid inclusions through quantifying the acceptable temperature excursion for preserving elastic behaviour: [l/(1 µm)]−0.64 × (90 °C), where l is the FI size. This threshold is lower for FIs close to the surface of the host crystal or to another FI. We also list ‘best practices’ for applying both microthermometry and Brillouin thermometry. Key Points A new halite fluid inclusions‐based palaeothermometer which determines parent brine temperature within 1 °C. Solution to the long‐standing debate on damage of halite fluid inclusions by quantifying the acceptable range of temperature excursion as a function of size. We list “best practices” for both microthermometry and Brillouin thermometry.